2012
DOI: 10.1002/qua.24182
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric degradation mechanisms of a simulant organophosphorus pesticide isopropyl methyl methylphosphonate: A theoretical consideration

Abstract: [a] Calculations using density functional theory were performed to explore the mechanisms for atmospheric degradation of isopropyl methyl methylphosphonate (IMMP). The potential energy surface profiles for OH-initiated reaction of IMMP were constructed, and all possible degradation channels were considered. Rate constants were further calculated using transition state theory. It was established from these calculations that H-abstractions from alkyl groups have much lower energy barriers than substitutions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This assertion is reinforced by experimental evidence indicating that reactions between O­( 3 P) and organic or hydrocarbon-based films proceed largely through such abstraction mechanisms. Second, and perhaps more importantly, while the initial abstraction by O­( 3 P) may be energetically limiting or rate-limiting, once a hydrogen has been abstracted, hydroxyl radicals are produced. These hydroxyl radicals can continue reacting within the film, and the barriers for hydrogen abstraction from DIMP by hydroxyl radicals are significantly lower. , One theoretical study concluded that abstraction from all three possible sites by hydroxyl radicals is facile under atmospheric conditions, with barriers at or below 2kT for our system . These low-barrier, secondary abstractions help explain why all of the DIMP C–H stretching peaks are observed to decrease concurrently despite the disparity in barriers for direct abstraction by O­( 3 P).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…This assertion is reinforced by experimental evidence indicating that reactions between O­( 3 P) and organic or hydrocarbon-based films proceed largely through such abstraction mechanisms. Second, and perhaps more importantly, while the initial abstraction by O­( 3 P) may be energetically limiting or rate-limiting, once a hydrogen has been abstracted, hydroxyl radicals are produced. These hydroxyl radicals can continue reacting within the film, and the barriers for hydrogen abstraction from DIMP by hydroxyl radicals are significantly lower. , One theoretical study concluded that abstraction from all three possible sites by hydroxyl radicals is facile under atmospheric conditions, with barriers at or below 2kT for our system . These low-barrier, secondary abstractions help explain why all of the DIMP C–H stretching peaks are observed to decrease concurrently despite the disparity in barriers for direct abstraction by O­( 3 P).…”
Section: Resultsmentioning
confidence: 71%
“…The fact that all three of these modes are observed to decrease in intensity indicates that the system has enough energy to overcome the barriers for reaction at each of the C–H sites visible in the RAIR spectra (P–CH 3 and C–CH 3 ). The tertiary C–H stretch of the isopropoxy group is unresolved in our spectra, but theoretical barriers for hydrogen abstraction are comparable for both possible sites on the isopropoxy groups, so the reaction is likely occurring at the tertiary site as well. ,, …”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations